El Alto, rebel city : self and citizenship in Andean Bolivia - Lazar, Sian (Latin America otherwise., 2008)
El Alto, Rebel City combines ethnography and political theory to explore the astonishing political power exercised by the indigenous citizens of El Alto, Bolivia in the past decade.